Long-Term Nitrogen, Phosphorus, and Potassium Fertilization of Irrigated Grain Sorghum - Alan J. Schlegel; H. Dewayne Bond (Kansas Agricultural Experiment Station Research Reports, 2020)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated grain sorghum in western Kansas. In 2019, N applied alone increased yields by 66 bu/a, whereas N and P applied together increased yields up to 85 bu/a. Averaged across the past 10 years, N and P fertilization increased sorghum yields up to 78 bu/a. Application of 160 lb/a N (with P) produced the maximum yield in 2019, which is slightly more than the 10-year average. Application of potassium (K) has had no effect on sorghum yield throughout the study period. Average grain N content reached a maximum of ~0.7 lb/bu while grain P content reached a maximum of 0.16 lb/bu (0.34 lb P2O5/bu) and grain K content reached a maximum of 0.19 lb/bu (0.23 lb K2O/bu). At the highest N, P, and K rate, apparent fertilizer recovery in the grain was 31% for N, 65% for P, and 38% for K.
Keywords: nitrogen fertilization; phosphorus fertilization; irrigated grain sorghum; long-term fertility; nutrient removal